Parental Attachment as Predictor of Delinquency - Maria Chong Abdullah; Lee Phaik Gaik; Habibah Elias; Jegak Uli (UUM Press, 2013)
Purpose â€" The purpose of this study is to find out the relationship between adolescentsâ€™ parental attachment and delinquent behaviour in the aspects of trust, communication and alienation. In this study, delinquent behaviour refers to the set of behaviours which is against any mainstream established rules or norms. It is believed that delinquent behaviour has the potential to cause school failure, impairments in socio-emotional development, peer rejection, and adult crime.   Methodology â€" Data were gathered from a sample of 300 secondary school students aged 15-18 years old in Selangor. These students were selected from the â€œhardcore schoolsâ€ which was obtained from the so called "hardcore schools" listed by the School Division for serious disciplinary problems. Two instruments, namely surveys on the â€œBehaviour of Studentsâ€ and â€œParental Attachmentâ€(PA) were utilized to collect the research data. The researchers employed correlational research design in this study.   Findings â€" Data showed that the highest delinquency among the adolescents was misbehaviour in school, followed by crime, vandalism, pornography, dishonesty and drugs. Results also revealed a negative linear relationship between parental attachment (r=-0.282,p=0.0001) and delinquent behaviour, implying that adolescents with better parental attachment had lower levels of delinquency. In addition, findings showed that adolescents trusted in their mothers (M=3.70,SD=0.63) more than they trusted in their fathers (M=3.51, SD=0.72) in relation to communication and alienation. It is suggested that close supportive parents and frequent communication between parents and their children serve to prevent adolescent delinquency.   Significance â€" This research is significant to parents, school, teachers, counselors and the community.